Modular structural elements in the replication origin region of Tetrahymena rDNA. - Du, C (1995)
Computer analyses of the DNA replication origin region in the amplified rRNA genes of Tetrahymena thermophila identified a potential initiation zone in the 5'NTS [Dobbs, Shaiu and Benbow (1994), Nucleic Acids Res. 22, 2479-2489]. This region consists of a putative DNA unwinding element (DUE) aligned with predicted bent DNA segments, nuclear matrix or scaffold associated region (MAR/SAR) consensus sequences, and other common modular sequence elements previously shown to be clustered in eukaryotic chromosomal origin regions. In this study, two mung bean nuclease-hypersensitive sites in super-coiled plasmid DNA were localized within the major DUE-like element predicted by thermodynamic analyses. Three restriction fragments of the 5'NTS region predicted to contain bent DNA segments exhibited anomalous migration characteristic of bent DNA during electrophoresis on polyacrylamide gels. Restriction fragments containing the 5'NTS region bound Tetrahymena nuclear matrices in an in vitro binding assay, consistent with an association of the replication origin region with the nuclear matrix in vivo. The direct demonstration in a protozoan origin region of elements previously identified in Drosophila, chick and mammalian origin regions suggests that clusters of modular structural elements may be a conserved feature of eukaryotic chromosomal origins of replication.